Performance of a rainwater harvesting tank under under varying non-potable demand: case study in Kubang Semang, Penang - Nurhidayati Mat Daud; Nur Fikriah Daud; Amalina Amirah Abu Bakar; Noraziyan Abd Aziz; Sabariah Badrealam; Zuraisah Dollah (Penerbit Universiti Kebangsaan Malaysia, 2023)
Rapid development and climate change has endangered the availability of water resources worldwide. This study look into the potential of the applying a rainwater harvesting system (RWHS) for non- potable water usage in a double-storey residential terrace house using Tangki NAHRIM 2.0 (TN2.0). TN2.0 is a web application that adopt the yield-after-spillage (YAS) convention to identify the optimum rainwater tank size. It is found that for a house of size 86.86 m2, the optimum tank size is 2 m3 with water-saving and storage efficiency values of 51% and 63.2% respectively. Additionally, the performance of the optimum tank size of 2 m3 was further examined under different water demand. It was found that a 2 m3 tank was still able to save water up to 42.1% for a family of 10 persons. Meanwhile, the storage efficiency shows a little increment from 63.2% to 67.8%